Graphene-based electrochemical sensor for detection of 2,4,6-trinitrotoluene (TNT) in seawater: the comparison of single-, few-, and multilayer graphene nanoribbons and graphite microparticles - Goh, Madeline Shuhua (2013)
The detection of explosives in seawater is of great interest. We compared response single-, few-, and multilayer graphene nanoribbons and graphite microparticle-based electrodes toward the electrochemical reduction of 2,4,6-trinitrotoluene (TNT). We optimized parameters such as accumulation time, accumulation potential, and pH. We found that few-layer graphene exhibits about 20% enhanced signal for TNT after accumulation when compared to multilayer graphene nanoribbons. However, graphite microparticle-modified electrode provides higher sensitivity, and there was no significant difference in the performance of single-, few-, and multilayer graphene nanoribbons and graphite microparticles for the electrochemical detection of TNT. We established the limit of detection of TNT in untreated seawater at 1 μg/mL.